Effectiveness of robot-assisted gait training on patients with burns: a preliminary study. Issue 12 (9th September 2020) - Joo, So Young; Lee, Seung Yeol; Cho, Yoon Soo; Lee, Kuem Ju; Kim, Sang-Hyun; Seo, Cheong Hoon
Abstract: Gait enables individuals to move forward and is considered a natural skill. However, gait disturbances are very common in patients with burn injury. Recent studies have emphasized the role of robot-assisted gait training (RAGT) in rehabilitation. This study aimed to evaluate the efficacy of RAGT on patients with lower extremity burn for the first time. 12 patients with lower extremity burns were included. SUBAR® (CRETEM, Korea) is a wearable robot with a footplate that assists patients to perform voluntary muscle movements. Patients underwent 30 min of RAGT using SUBAR ® for 30 min once a day for 5 days a week for 4 weeks. Functional scores of functional ambulation category (FAC), 6-minute walking test (6MWT) distances, and numeric rating scale (NRS) scores of pain before and after 4 weeks RAGT were measured. NRS scores decreased significantly from 6.92 ± 1.78 points before RAGT to 4.17 ± 1.75 points after 4 weeks of RAGT ( p  = 0.002). FAC scores increased significantly from 1.58 ± 1.08 points to 3.08 ± 1.31 points ( p  = 0.002). 6MWT scores increased significantly from 182.17 ± 153.62 points to 279.17 ± 119.27 points ( p  = 0.001). RAGT may facilitate early recovery from a burn injury. This study is the first study to evaluate the effectiveness of RAGT on patients with burns. Outcomes were meaningful, including patient-subjective outcome measures, and objective gait functions for burn patients. The absence of complications on burn patients provides an opportunity to enlarge the application area of RAGT.